PENALARAN ANALOGI SISWA BERDASARKAN TAHAPAN CLEMENT PADA MATERI DIMENSI TIGA DI SEKOLAH MENENGAH ATAS - Nurul Innayah; Agung Hartoyo; Bistari Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe purpose of this research was to describe students' analogical reasoning based on Clement's stages in three-dimensional material at SMA Negeri 3 Pontianak. The method in this research was descriptive method with a case study research form. The subjects in this study were eight students of class XII IPA 3 SMA Negeri 3 Pontianak. The results of the analogy reasoning test showed that students of class XII IPA 3 SMA Negeri 3 Pontianak had analogous reasoning based on the low Clement stage, were of the four stages, namely the Generating the Analogy stage, the Evaluating the Analogy Relation stage, the Understanding the Analogy Case stage and the Transferring Findings stage can only be reached by two students. In Generating the Analogy stage, six students can reach it. Evaluating the Analogy Relations stage can be achieved by four students. Understanding the Analogy Case stage can be achieved by three students. Meanwhile, the Transferring Findings stage can be achieved by two students. Keywords: Reasoning Analogy, Stages of Clement